Incorporating polyacrylamide-functionalized graphene nano-additive enables pilot-scale preparation of mechanically reinforced viscose staple fiber. (April 2021) - Pan, Liang; Fei, Xiang; Yang, Lijun; Zhou, Zhe; Zhu, Meifang
Abstract: Herein, we communicate an effective method for pilot-scale preparation of graphene reinforced viscose staple fiber. Via an in-situ polymerization approach, the polyacrylamide (PAM) was firstly grafted on the surface of graphene oxide (PAM-GO). It was then reduced by ascorbic acid into the PAM-rGO nanosheets, featuring good dispersibility and compatibility with the viscose matrix. Subsequently, using the viscous process, the viscous/PAM-rGO composite fiber on the pilot scale. When compared to the pure viscous fiber, the tensile strength and Young''s modulus of the viscose/PAM-rGO composite fiber that loaded with 1.0 wt% PAM-rGO demonstrated a significant by 170% and 314%. Comparing the experimental results and the Halpin-Tsai theoretical simulation indicated that most of the incorporated PAM-rGO nanosheets aligned along the fiber axis direction. It was further evidenced by calculating Herman's orientation factor ( f ) of the viscous/PAM-rGO fibers. Additionally, strong non-covalent interactions dominated by hydrogen bonding between the cellulose and PAM-rGO were demonstrated by Raman and FTIR analysis. Furthermore, incorporating PAM-rGO into the cellulose matrix has also improved the thermal stability of the composite fiber. Therefore, we assume that this study will open a new pathway for the scale-up preparation of -incorporated multifunctional polymer fibers. Graphical abstract: Unlabelled Image Highlights: Polyacrylamide functionalized graphene (PAM-rGO) was successfully fabricated via an in-situ polymerization method. The poly(vinyl alcohol)-assisted cellulose sulfonate/ PAM-rGO solution with an excellent spinnability was achieved. The viscose/PAM-rGO composite fibers with significantly enhanced mechanical properties were produced on the pilot scale.